2019
DOI: 10.32098/mltj.03.2015.01
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of a biological augmentation of rotator cuff repairs using a collagen implant: a 2-year MRI follow-up

Abstract: Preliminary investigation of a biological augmentation of rotator cuff repairs using a collagen implant: a 2-year MRI follow-up tissue matured over time and became indistinguishable from the underlying tendon. At 24 months all repairs remained intact and normal footprint anatomy of the tendon was restored in all patients. All clinical scores improved significantly over time. Conclusion: the ability of a collagen implant to induce new host tissue formation and restore the normal footprint anatomy may represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…An experimental study in sheep has demonstrated the ability of a highly-porous, low modulus, reconstituted collagen implant to consistently increase the thickness of a rotator cuff tendon by inducing the formation of a well-integrated and mature tendon-like tissue 22 . In addition, a recent clinical study has demonstrated the ability of this collagen implant to increase the thickness of the supraspinatus tendon following augmentation of full-thickness, rotator cuff repairs 23 . Therefore, the purpose of the current clinical study was to evaluate the effect of this implant placed arthroscopically on the bursal surface of the supraspinatus tendon in patients with partial-thickness tears.…”
Section: Evidence Of Healing Of Partial-thickness Rotator Cuff Tears mentioning
confidence: 99%
See 3 more Smart Citations
“…An experimental study in sheep has demonstrated the ability of a highly-porous, low modulus, reconstituted collagen implant to consistently increase the thickness of a rotator cuff tendon by inducing the formation of a well-integrated and mature tendon-like tissue 22 . In addition, a recent clinical study has demonstrated the ability of this collagen implant to increase the thickness of the supraspinatus tendon following augmentation of full-thickness, rotator cuff repairs 23 . Therefore, the purpose of the current clinical study was to evaluate the effect of this implant placed arthroscopically on the bursal surface of the supraspinatus tendon in patients with partial-thickness tears.…”
Section: Evidence Of Healing Of Partial-thickness Rotator Cuff Tears mentioning
confidence: 99%
“…The reconstituted collagen scaffolds were made from highly-purified, type I collagen from bovine tendons using proprietary methods (Collagen Matrix, Inc., Oakland, New Jersey) 22,23 . The collagen fibers were processed to create a highly oriented and highly porous (85-90% porosity) collagen scaffold with a DNA content of less than 50 ng/mg 22,23 . The scaffolds were freeze-dried after processing and rehydrated at the time of surgery 22,23 .…”
Section: Collagen Implantmentioning
confidence: 99%
See 2 more Smart Citations
“…Sheep studies by Van Kampen et al have shown that placing a highly-porous collagen implant on the bursal surface of the infraspinatus tendon would induce the formation of a fibrovascular tissue resem- bling tendon and result in a significant and consistent thickening of the infraspinatus tendon (23). Following the animal experiments and the finite element studies, the porous collagen implant was used in humans to treat partial thickness cuff tears, and also as an augment to the treatment of full thickness cuff tears (11,24). Subsequent published tissue retrieval studies confirmed that the histological changes seen in human specimens corresponded precisely with the findings of the sheep study of Van Kampen et al (23,25).…”
Section: Discussionmentioning
confidence: 99%